Phylogenetic relationships among the taxa of the genus Johrenia DC. (Apiaceae) from Turkey based on molecular method (Bangladesh Journal of Plant Taxonomy, 2010)
In the present study, ISSR markers were employed to determine the phylogenetic relationships among the taxa of Johrenia. The genera Angelica and Xanthogalum were selected as outgroups. Unweighted pair group method with arithmetic mean (UPGMA) and Principal Coordinate Analyses were conducted to view the molecular relationships. Johrenia alpina, J. depauperatum and J. aurea are transferred to the genus Dichoropetalum. The infrageneric and intergeneric phylogenetic relationship among the Johrenia and Dichoropetalum genera are determined.Keywords: Johrenia; Dichoropetalum; Apiaceae; Taxonomy; ISSR; Turkey.DOI: 10.3329/bjpt.v17i2.6693Bangladesh J. Plant Taxon.17(2): 113-120, 2010 (December)